The soils of Wisconsin - Bockheim, James G.; Hartemink, Alfred E., 1964- (Springer, 2017)
This book provides an up-to-date and comprehensive report on the soils of Wisconsin, a state that offers a rich tapestry of soils. It discusses the relevant soil forming factors and soil processes in detail and subsequently reviews the main soil regions and dominant soil orders, including paleosols and endemic and endangered soils. The last chapters address soils in a changing climate and provide an evaluation of their monetary value and crop yield potential. Richly illustrated, the book offers both a valuable teaching resource and essential guide for policymakers, land users, and all those interested in the soils of Wisconsin.
Keywords: Soils -- Wisconsin.; Wisconsin.; elektronické knihy; electronic books